ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN MELALUI CITRA RESTORAN SEBAGAI VARIABEL INTERVENING - Hanani, Zati; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2018)
The  purpose  of this  study is to explain the effect of product quality, service quality and restaurant  atmosphere  to influence  purchase  decisions,  where    restaurant  image  is used as  an intervening variable to the purchase decision at Pondok Ijo Weleri Kendal Restaurant.This  research  is  done  by  taking  sample  using  purposive  sampling  technique,  that  is consumers  who have visited and bought some food in Pondok Ijo Restaurant at least once with average  of age  14 years old up to 40 years and above. Data collection was obtained from 100 consumers  of  Pondok  Ijo  Restaurant  by giving questionnaires  which consist  of open questions which  is  analyzed  qualitatively,  and  the  answer  of  the  closed  questions  were  analyzed  using Multiple  Linear regression method using SPSS 22 program.The results of the analysis show that product quality, service quality and store atmosphere have  a  positive  and significant  influence  on the  restaurant  image, then restaurant  image  has  a positive and significant  influence on purchase decisions.